Multiscale polymer composites : a review of the interlaminar fracture toughness improvement - Bhudolia, Somen Kumar (2018)
Composite materials are prone to delamination as they are weaker in the thickness direction. Carbon nanotubes (CNTs) are introduced as a multiscale reinforcement into the fiber reinforced polymer composites to suppress the delamination phenomenon. This review paper presents the detailed progress made by the scientific and research community to-date in improving the Mode I and Mode II interlaminar fracture toughness (ILFT) by various methodologies including the effect of multiscale reinforcement. Methods of measuring the Mode I and Mode II fracture toughness of the composites along with the solutions to improve them are presented. The use of different methodologies and approaches along with their performance in enhancing the fracture toughness of the composites is summarized. The current state of polymer-fiber-nanotube composites and their future perspective are also deliberated.